General description of subroutines for solving ordinary differential equations from the Numerical Analysis Library (Research Computer Center, Moscow State University) - Arushanian, O.B.; Zaljotkin, S.F. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
Solution of ordinary differential equations with the Numerical Analysis Library developed at the Research Computer Center of Moscow State University is discussed.